Work Readiness of Final Year Students Observed from Grit and Career Adaptability - Diva, Vivianora; Satwika, Pratista Arya (Jurnal Kajian Bimbingan dan Konseling, 2024)
Universities are obliged to prepare graduates of the highest caliber and ensure that their qualifications align with the requirements of the professional world. Therefore, it is essential for them to equip students with the necessary skills and knowledge before they enter the workforce. Nevertheless, a considerable number of students remain inadequately prepared for the demands of the workplace. The capacity to persevere and adapt to new circumstances are two key attributes that can influence an individual's preparedness for professional roles. This study aims to ascertain the relationship between grit and career adaptability with the work readiness of final-year students. This study employed a quantitative methodology, with 136 students selected through the use of a simple random sampling technique. The data collection method employed three scales: the Work Readiness Scale (α = 0.827), the Grit-12 Scale (α = 0.738), and the Career Adaptabilities Scale (α = 0.963). Subsequently, the data were analyzed using multiple linear regression. The results demonstrated that both grit and career adaptability exerted a significant influence on work readiness in final-year students, both concurrently and partially (p < 0.05). Grit and career adaptability collectively contributed an effective 50.1% to work readiness. Consequently, it is recommended that students cultivate persistence and the capacity to adapt their careers, in order to enhance their readiness to enter the workforce.